Investigation of usability of limonite aggregate in heavy-weight concrete production - Esen, Yuksel; Dogan, Zulfu Murat (Pergamon-Elsevier Science Ltd, 2018)
Limonite (Fe2O3.xH(2)O) is a soft or brown, hard iron mineral, usually in yellow colour. It is also used as a pigment since it contains iron ore. It is believed that it can also be used in the production of heavy concrete due to its 60% iron ore content. In this paper, an experimental study was carried out on radiation shielding properties and certain physical and mechanical properties of normal and limonite reinforced concrete. For this purpose, with the normal concretes prepared according to standards, amounts of aggregates were reduced at the rates of 20%, 40%, 60%, 80% and 100% by volume respectively, and heavy concrete mixes were prepared that were obtained by adding limonite at the same rates in their place. With limonite reinforcement, compressive and flexural strength of the concrete produced decreased, water absorption amount increased and their radiation permeability significantly decreased.
Keywords: Limonite.; Heavy-weight concrete; Radiation shielding; Physical properties